Flavonoid-containing supplements for preventing acute respiratory tract infections: A systematic review and meta-analysis of 20 randomized controlled trials. (November 2022) - Yao, Jia; Zhao, Jia; Wen, Jun-Ru; Yang, Zhao-Jun; Lin, Yu-Ping; Sun, Lu; Lu, Qi-Yun; Fan, Guan-Jie
Abstract: Background: This systematic review and meta-analysis was conducted to investigate the efficacy and safety of flavonoid-containing supplements in preventing acute respiratory tract infection (ARTI). Methods: Randomized controlled trials (RCTs) investigating the effects of flavonoid-containing supplements on ARTI prevention in the aspects of ARTI incidence, mean ARTI sick days, symptoms, bio-immune markers, and adverse effects were searched in 5 databases. Data were searched from inception to November 26, 2021. Stata 16.0 was used to perform the meta-analysis. Results: Twenty RCTs (n = 4521) were included in this systematic review and meta-analysis. Pooled results showed that in the flavonoid-containing supplement group, the ARTI incidence and mean ARTI sick days were significantly decreased compared to those in the control group (RR = 0.81, 95% CI: 0.74–0.89, p  < 0.001; WMD = −0.56, 95% CI: −1.04 to −0.08, p  = 0.021; respectively). In 8 RCTs, flavonoids were singly used for interventions, ARTI incidence in the experimental group significantly decreased compared to that in the control group (RR = 0.85, 95% CI: 0.72–1.00, p  = 0.047). In ten RCTs, flavonoid-containing mixtures were applied for interventions, and ARTI incidence in the experimental group significantly decreased compared to that in the control group (RR = 0.79, 95% CI: 0.71–0.89, p  < 0.001). Furthermore, the ARTI incidence and mean ARTI sick days were significantly decreased in the experimental group compared to those in the control group in the flavan-3-ols subgroup (RR = 0.79, 95% CI: 0.67–0.92, p = 0.002; WMD = −2.75, 95% CI: −4.30 to −1.21, p  < 0.001; respectively) and the multiple subclasses subgroup (RR = 0.75, 95% CI: 0.63–0.88, p  = 0.001; WMD = −0.56, 95% CI: −1.11 to −0.01, p  = 0.046; respectively). However, the bio-immune markers including interleukin-6, hypersensitive-c-reactive-protein, tumor necrosis factor-α, and interferon-γ did not differ between the flavonoid group and the control group. Moreover, in the flavonoid-containing supplement group, the incidence of adverse reactions did not increase compared to that in the control group (RR = 1.16, 95% CI: 0.78–1.73, p  = 0.469). Conclusions: This systematic review and meta-analysis showed that flavonoid-containing supplements were efficacious and safe in preventing ARTIs. The most important limitations result from the small number of trials, poor quality of some included RCTs, differences in the composition and types of interventions, principal subclasses of flavonoids, methods of administration, and methodology. Moreover, only a few RCTs conducted independent verification of the flavonoid supplements used in the trial in terms of purity and potency, which may lead to a potential source of bias. Thus, larger and better-designed studies are needed to further verify this conclusion. Graphical Abstract: ga1 Highlights: Flavonoid-containing supplements were efficacious and safe in preventing ARTI. Flavonoid-containing mixtures and flavonoids singly-used could decrease ARTI incidence. Flavonoid-containing supplements did not increase the adverse reactions. Limitations included the limited number and quality of trials, differences in the flavonoid types and methodology. Few RCTs conducted independent verification of purity and potency of flavonoids, which may lead to a potential bias.